Deviating memories: Armando Lulaj’s seriously playful excursions into Albania’s history - Grgic, Ana (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
This paper examines how certain contemporary audio-visual works from post-socialist countries in the Balkan region, employ archival footage from the communist period, to address and problematize the notion of remembering and suppressing national history through collective memory. I specifically focus on the work of the Albanian artist, Armando Lulaj and his videos Albanian Trilogy: A Series of Devious Stratagems (2011, 2012 and 2015) exhibited at the 56th Venice Biennale. By re-using images and narratives produced during Enver Hoxha’s regime, and still ingrained in Albanian visual memory, these films provide alternative readings of Albanian history from the Cold War to the present day. What is more, some of this archival material is made public for the first time, while the rest has been dormant and purposely forgotten in archival vaults. Lulaj’s playful excursions, create connections between a problematic and suppressed past and the difficult and selective present, by juxtaposing evocative and politically charged visual records and contemporary footage of artist’s commissioned performances.